2001
DOI: 10.1016/s0006-3495(01)75822-5
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Alamethicin in Oriented Phospholipid Bilayers Determined by 15N Solid-State Nuclear Magnetic Resonance

Abstract: The conformation of the 20-residue antibiotic ionophore alamethicin in macroscopically oriented phospholipid bilayers has been studied using (15)N solid-state nuclear magnetic resonance (NMR) spectroscopy in combination with molecular modeling and molecular dynamics simulations. Differently (15)N-labeled variants of alamethicin and an analog with three of the alpha-amino-isobutyric acid residues replaced by alanines have been investigated to establish experimental structural constraints and determine the orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
121
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 84 publications
(132 reference statements)
17
121
0
3
Order By: Relevance
“…In the voltage-dependent partitioning model, partitioning of the peptide between the membrane and aqueous phase requires diffusion of the peptide into the membrane. However, our calculations, and experiments [5,33,35,37,38], show that ALM strongly partitions into the membrane regardless of voltage.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the voltage-dependent partitioning model, partitioning of the peptide between the membrane and aqueous phase requires diffusion of the peptide into the membrane. However, our calculations, and experiments [5,33,35,37,38], show that ALM strongly partitions into the membrane regardless of voltage.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, slight differences in experimental setup might tip the balance towards one or the other. 15N NMR studies showed a tilted orientation of ALM in the bilayer in the nonconductive state [38]. The tilt was between 10°and 20°.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the transmembrane region of the related M2 polypeptide of influenza A has been investigated by solid-state NMR spectroscopy (62 (15,64,65) and the putative channel-lining sequence M2 of the acetyl choline receptor (35). In recent years there has been considerable interest in exploring the utility of natural antibiotic peptides by themselves or as templates to design derivatives for pharmaceutical use (66).…”
Section: Solid-state Nmr Spectroscopy Of Membrane-associated Peptidesmentioning
confidence: 99%
“…From the anisotropic 15 N chemicalshift data and 1 H-15 N dipolar couplings determined for alamethicin with 15 N-labeled Ala6, Val9, and Val15 incorporated into a phospholipid bilayer at a peptide-to-lipid molar ratio of 1:8, it was determined that alamethicin assumes a largely linear α-helical structure that spans the membrane with the molecular axis tilted by 10-20°relative to the bilayer normal. In particular, the compatibility with a straight α-helix was tilted by 17°and a slightly kinked MD structure was tilted by 11°relative to the bilayer normal [127]. Measurement of the orientation-dependent 1 H-15 N dipole-dipole coupling, 15 N anisotropic chemical shift, and 2 H quadrupole coupling parameters for a single residue, combined with analysis of the anisotropic interaction for the Aib8 residue, provided detailed information regarding the helix-tilt angle, wobbling, and oscillatory rotation around the helical axis in the membrane-bound state of alamethicin [73].…”
Section: Alamethicinmentioning
confidence: 99%